Acoustic and mechanical properties of recycled polyvinyl chloride/ground tyre rubber composites. (April 2014) - Colom, X; Cañavate, J; Carrillo, F; Lis, MJ
In order to provide another way of reducing the stock of used tyres and polyvinyl chloride waste, a new material is developed and studied. Formulation includes a matrix constituted by a compound of recycled polyvinyl chloride with plasticized polyvinyl chloride and a reinforcement of ground tyre rubber. Acoustic and mechanical properties of different compositions of polyvinyl chloride/ground tyre rubber were tested in order to determine their suitability for applications fulfilling industry requirements. Sound absorption has been analyzed, showing interesting results at frequencies higher than 2500 Hz. The obtained values are found to be depending on the thickness of the sample, the content of the ground tyre rubber and the existence of gaps, pores and voids either between layers or in the interphase between the matrix and reinforcement. From the study of the mechanical properties, we may observe that the ground tyre rubber act as filler, improving stiffness of polyvinyl chloride/ground tyre rubber composites with an increase of Young Modulus. The tensile strength, elongation at break and toughness decrease slowly. The decrease of these mechanical properties is observed to be lower than in the case of composites made by using high-density polyethylene as a matrix.